El papel de la insulina en la regulación de la síntesis de proteínas lácteas en bovinos - Correa Cardona, Héctor Jairo; Echeverri R., Nancy P. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In spite of the nutritional and industrial importance of milk proteins the mechanisms that control their synthesis and concentration still are not completely understood. Among the different hormones that participate in the mammary gland metabolism, insulin has received higher attention due to its close relationship with the energetic and protein metabolism in dairy cows and to its marked effect on the production and concentration of milk proteins. There are at least three mechanisms by which this hormone seems to contribute to increase in the synthesis and concentration of milk protein that are reviewed in this paper: nutrient distribution to mammary gland, regulation of gene expression of caseins and the rate of initiation of protein synthesis at post-transcriptional level.